1 - Oil and Security in Nigeria: The Niger Delta Crisis: Olayiwola Owolabi - Okwechime, Iwebunor; Olayiwola Owolabi, (Africa Development, 2007)
This paper examines oil and security in Nigeria, with special reference to the crisis-ravaged Niger Delta. Its focus on the Niger Delta and its festering crisis stems from that region’s critical importance to Nigeria. As the nation’s treasure base, the Niger Delta provides over 80 percent of government revenues, 95 percent of export receipts, and 90 percent of foreign exchange earnings. Also, the bulk of Nigeria’s bio-diversity and some of her best human resources are derived from the Niger Delta. This paper posits that beyond the well-known threats to the security of the Nigerian state, the lingering crisis in the country’s oil- producing areas is a grave threat to human security in that region. Since poverty, environment and food security are key to national security, the ruthless exploita- tion and destruction of the natural environment upon which the inhabitants of the Niger Delta depend for their livelihood and sustenance pose major threats to human security in that region and, by implication, to the Nigerian state. The paper suggests that to resolve the crisis, government policy on petroleum should be more inclusive, taking into consideration the peculiar problems and needs of the oil-producing areas, as well as those of the Nigerian state and the oil indus- try itself.